IMPLEMENTASI MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN DI KELAS IX MTs AL-FALAH - Akbar, Rofiq Faudy; Maezida, Ikmalatul Ghina; Sofiana, Dila Lady (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to overcome the problems of class IX C IPS students by using the PBL model to discuss globalization. This classroom action research topic discusses constructivist learning theory. The research method uses qualitative research through primary and secondary data sources. The results of research on the PBL model at MTs Al-Falah can improve learning outcomes for social studies subjects in class IX C. The application of the problem-based learning model uses a projector as a tool, while PowerPoint and films are used as learning materials. In cycle I, the explanation and learning conditions using the PBL model were not optimal, and cycle II was able to carry out learning activities well.